The Effects of the Covid-19 Outbreak on the Positive Development of Young People in Malamulele, South Africa - Thulani Andrew Chauke; Rachel Chinyakata (The Thinker)
The advent of the Covid-19 pandemic has brought dire social, economic, physical and mental health consequences worldwide (World Health Organization, 2020). The rapid increase of Covid-19 infections and fatalities has caused much concern around the world and has resulted in the implementation of various mitigation measures. Covid-19 has taken everyone by surprise, and disrupted the world’s economy tremendously.